Adult Education and Entrepreneurial Sustainable Development in Nigeria: A study of Akwa Ibom State Agency for Adult and Non-Formal Education (2007-2023) - Ekpo , Michael Eugene; Umoh, Ubong Etim; Udoaka , Stephen Pius (Covenant Journal of Entrepreneurship, 2024)
Education is the key to human and national development in modern globalized and highly technological world of the 21st Century. Through education, information, communication, technology, innovation, entrepreneurial skills are developed and transferred across the globe for sustainable development. Adult education is one aspect of education introduced in Nigeria to tackle the problem of high rate of illiteracy particularly amongst the adults who could not afford formal education. Adult education is targeted at ensuring education for all by 2030. It involves basic literacy, post-literacy and vocational training programmes, which add values to entrepreneurship in Nigeria. The study identified as its objective gaps in adult education programmes and its impact on entrepreneurial sustainable development in Akwa Ibom State, and provided remedial to the gaps. Descriptive and Survey methods were employed to administered 10 items questionnaire on the respondents from 9 selected centres, 3 from each senatorial district out of 888 adult education Centre’s with sample size of 126 using stratified sampling technique. Simple percentage and tabular presentation were adopted for data presentation and analysis while secondary data analyzed contextually. The study among others revealed that Adult education have significant and direct impact on entrepreneurial sustainable development in Akwa Ibom State by building individual skills/knowledge for SMEs and self-empowerment, job creation/employment opportunities, and outlined its challenges/weaknesses to include: inadequate funding of the programmes, policy inconsistency at the implementation stage, lack of teachers’ qualification, low learners enrollment, lack of learning materials and infrastructures etc. It concluded there is need to strengthen Adult and non-formal education for effective entrepreneurial sustainable development in Akwa Ibom State and by extension Nigeria. It recommended proper funding of Adult education, training of teachers and facilitators, proper monitoring and evaluation of the programmes to prevent corruption, empowerment/employment opportunities should be offered to Adult learners by various level of governments.